Intervensi Sosial Komunitas Birmingham Owner’s Motorcycle Siantar - Fajar Utama Ritonga; Adil Arifin; Tuti Atika (PERSPEKTIF, 2020)
This research purpose to describe the social intervention of the Birmingham Small Arm Owner Motorcycle Siantar (BOM'S) community in fighting for pedicabs with the Birmingham Small Arm (BSA) motorbike brand as a means of transportation for tourists. The research method was carried out with a qualitative approach, the informants in the study were the key informants and 4 main informants. The location of the study was carried out in Pematangsiantar City. The results of this study describe social intervention by the Birmingham Small Arm Owner Motorcycle Siantar (BOM'S) with 4 demands called the " Empat Tuntutan Rakyat Bikers Becak Siantar ", with demonstration activities, besides the community also conducts social activities such as touring, tourism promotion in Pematangsiantar City. antique motorbike exhibitions, cultural arts performances, and the next action was the construction of the Becak Siantar monument in the Siantar City Square in 2018, which featured the Siantar pedicab with the Birmingham Small Arm/BSA brand motorbike as an icon of the Pematangsiantar City. The conclusion of this study is a model of social community intervention that is carried out using a model of social action and community development.